Formation of highly-porous biomorphous SiC-ceramics derived from cellulose paper - Fey, Tobias; Sieber, Heino; Greil, Peter (2005)
Highly-porous SiC-ceramics were prepared by pyrolysis and reactive conversion of Si-powder / resin coated cellulose fiber papers in inert atmosphere at temperatures between 1300-1500 degrees C. The reactive phase formation during annealing was monitored by XRD and TGA/DTA measurements. The morphology of the initial cellulose fiber paper, the coated paper and the final beta-SiC-ceramic was characterized by SEM/EDX, density and porosity measurements. After processing, the highly-porous SiC-ceramics are characterized by an unique Re-like morphology resulting from the initial cellulose like template.